PENGARUH MOTIVASI KERJA, MANAJEMEN WAKTU, DAN STRES KERJA TERHADAP KINERJA PERKERJA PARUH WAKTU YANG BERSTATUS MAHASISWA DI MAGELANG - Prasetya, Miftachul Huda Adi; Alkadri Kusalendra Siharis (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This study aims to look at the effect of work motivation, time management, and work stress on the performance of part-time student workers in Magelang and provide references related to improving part-time student performance for part-time students and business owners. This study uses a quantitative methodology. 60 people were studied using a purposive sampling technique. Multiple regression analysis was performed for data analysis. The test results show that work motivation has a sizable positive impact on the performance of part-time students. Part-time student workers will be motivated to work effectively, thereby increasing their performance, if they have goals to achieve and a sense of purpose.